APPLICATION OF LACTATION PERSISTENCY COEFFICIENT FOR CALCULATION OF FULL LACTATION (305 DAYS) USING SHORT LACTATION DATA - Matvieiev М. А. (Scientific Progress & Innovations, 2020)
Early prediction of dairy cow productivity is necessary to select the most valuable individuals as early as possible and minimize the costs of maintaining and feeding low performing animals. In order to predict milk yield for full lactation, a method based on the application of lactation persistency coefficient for dairy cows of Holstein breed under the conditions of Ukrainian industrial farm was used. Also the feasibility of this method for early estimation of heifers with breeding purpose was carried out. Lactation persistency coeffi-cient was calculated using 146 cows' productivity data. The evaluation of the efficiency of applying this coef-ficient was conducted on 19 cows with known full lactation. The predicted productivity results, calculated after each month of lactation, were compared with the actual data, obtained as a result of control milking. Comparisons were performed 1) to determine the accuracy of prediction method and 2) to evaluate the pos-sibility of early selection of heifers based on the obtained prediction. To fulfill the first task, the comparisons of predicted values with actual data (Lac-T program data) using Lin's Concordance Correlation Coefficient (rc) were made. Lin's Concordance Correlation Coefficient was calculated using the MedCalc program mathematical tools. Spearman’s rank correlation coefficient (rs) was used to fulfill the second task. Produc-tivity prediction after the third control milking was the least accurate (rc=0.7583), and after the 7th month of lactation, the prediction was the most accurate (rc=0.9915–0.9991). The highest values of rank correlation coefficient were also obtained after the 7th month of lactation and up to the 9th month (rs=0.92–0.94). As a result of the calculations, it can be concluded that the proposed method can be applied after the 7th month of lactation (control milking). For further calculations, it is planned to expand the existing database of cow productivity and apply this method to other dairy cattle breeds.